2017
DOI: 10.3390/ma10080947
|View full text |Cite
|
Sign up to set email alerts
|

Update on Monoterpenes as Antimicrobial Agents: A Particular Focus on p-Cymene

Abstract: p-Cymene [1-methyl-4-(1-methylethyl)-benzene] is a monoterpene found in over 100 plant species used for medicine and food purposes. It shows a range of biological activity including antioxidant, anti-inflammatory, antinociceptive, anxiolytic, anticancer and antimicrobial effects. This last property has been widely investigated due to the urgent need for new substances with antimicrobial properties, to be used to treat communicable diseases whose diffusion in developed countries has been facilitated by globaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
155
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(167 citation statements)
references
References 81 publications
7
155
1
4
Order By: Relevance
“…In the present study, monoterpenes, such as alcohols, phenols, ketones, acetates and aldehydes, showed potential as natural fungicidal agents [14,16]. This study appraised the biological activities of 20 monoterpenes (alcohols, acetates, and aldehydes) against B. dothidea.…”
mentioning
confidence: 77%
“…In the present study, monoterpenes, such as alcohols, phenols, ketones, acetates and aldehydes, showed potential as natural fungicidal agents [14,16]. This study appraised the biological activities of 20 monoterpenes (alcohols, acetates, and aldehydes) against B. dothidea.…”
mentioning
confidence: 77%
“…Our study confirmed thymol and carvacrol as main constituents of the EOs with the best antibacterial activity: 40.5% of thymol in T. vulgaris and 38.2% and 66.5% of carvacrol in S. montana and O. vulgare, respectively. Moreover, T. vulgaris and S. montana EOs had the highest amount of p-cymene (19.4% and 14.8%, respectively), a monoterpene compound with antimicrobial properties [39].…”
Section: Discussionmentioning
confidence: 99%
“…( Andrade & de Sousa, 2013;Chouksey et al, 2010;de Sousa, Mesquita, de Araújo Ribeiro, & de Lima, 2015) ρ-Cymene Anxiolytic, antioxidant, anticancer, antinociceptive, anti-inflammatory, and antimicrobial effects (Chouksey et al, 2010;Marchese et al, 2017) Linalool Local anesthetic activity, antimicrobial activity, anti-inflammatory, antinociceptive, antihyperalgesic activities (Chouksey et al, 2010;Peana, Moretti, Watson, & Preedy, 2008) (…”
Section: α-Pinenementioning
confidence: 99%